PENGARUH MODEL PEMBELAJARAN DAN KEMANDIRIAN BELAJAR TERHADAP HASIL BELAJAR SISWA KELAS X SMA KRISTEN 1 KALABAHI - Selly, Alboin (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2023)
This study aims to see the effect of learning models and independent learning on learning outcomes in class XI SMA Kristen 1 Kalabahi. The method used in this study uses experimental research method with a 2x2 factorial design. with two forms of treatment which then become independent variables in this study, namely the learning model which is divided into 2 types, namely the model Problem Based Learning of and Coperative Learning, and Independent Learning. Data collection techniques use test instruments and non-test instruments with useful data analysis Descriptive statistics are presented in the form of frequency distribution tables and histograms. Furthermore, to test the first hypothesis, statistical analysis was used, namely the analysis of variance known as ANAVA, while to test the second hypothesis, the analysis of the mean difference test was used. For the third and fourth hypotheses, a one-party average different test analysis was used. The research results show that 1)Model problem based learning more effectively implemented than model coperative learning in improving student outcomes; 2) Students with high learning independence can improve student learning outcomes; 3) There is an interaction effect between learning models and independent learning on student learning outcomes; 4) Students with high learning independence, model problem based learning more effectively used than model coperative learning in improving student learning outcomes; 5) Application model problem based learning, students who have high learning independence are more effective than students who have low learning independence in improving student learning outcomes.